Value creation in banking through strategic alliances and joint ventures - Amici, Alessandra; Fiordelisi, Franco; Masala, Francesco; Ricci, Ornella; Sist, Federica (Journal of Banking & Finance, 2013)
A large number of studies (DeYoung et al., 2009) analyze merger outcomes in the financial industry, while other forms of business cooperation are still poorly investigated. Our paper examines results of strategic alliances and joint ventures in European and US banking over the period 1999–2009. First, we estimate abnormal returns around the deal announcement date and then these are regressed on a large set of explanatory variables. We show that joint ventures create shareholder value when involving non-banking financial partners and allowing banks to expand abroad, while international strategic alliances tend to destroy shareholder value.